2002
DOI: 10.1046/j.1365-2516.2002.00680.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiographic scores in haemophilic arthropathies: how well do these correlate to subjective pain status and daily activities?

Abstract: Haemophilic patients who reached adulthood before the establishment of prophylactic treatment frequently show multiple and substantial arthropathies. The aim of this study was to determine to what extent haemophiliac's subjective impairment due to arthropathies correlates with objective clinical and radiographic parameters. By means of a questionnaire and a visual analogue scale, we consulted 79 haemophiliacs concerning their joint-pain status, how these were treated and to what extent their daily activities h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 18 publications
3
46
1
Order By: Relevance
“…The mean values of both legs reached a 32.76% and a 30.56% according to the Pettersson's and Gilbert's scores, respectively. These values are in agreement with those reported by Wallny et al [3], who stated that knees suffer from a larger number of injuries, which can be aggravated due to the fact that they also support the body weight.…”
Section: Discussionsupporting
confidence: 93%
“…The mean values of both legs reached a 32.76% and a 30.56% according to the Pettersson's and Gilbert's scores, respectively. These values are in agreement with those reported by Wallny et al [3], who stated that knees suffer from a larger number of injuries, which can be aggravated due to the fact that they also support the body weight.…”
Section: Discussionsupporting
confidence: 93%
“…Studies have confirmed that patients with inhibitors experience greater ROM limitations and joint pain at an earlier age than those without inhibitors 3,4,15. Patients with high-titer inhibitors clearly demonstrate worse clinical and radiological joint scores than patients without inhibitors, and a three-fold increased risk of disability,3,4,12 due to more rapidly progressive joint disease 2,11,16…”
Section: Physical Impact Of Inhibitors In Patients With Hemophiliamentioning
confidence: 95%
“…Hemophilic arthropathy is an ongoing cumulative process that eventually results in damaging joint effects 811. The long-term effects on joints include limited range of motion (ROM), deformity, crippling disability, and chronic pain 3,4,1214.…”
Section: Physical Impact Of Inhibitors In Patients With Hemophiliamentioning
confidence: 99%
“…The elbow, knee and ankle joint were chosen to measure because these joints are the frequently affected joints in haemophilia [7,8]. Children were asked to actively stretch or bend the joint maximally without interference by the investigator.…”
Section: Measurement Proceduresmentioning
confidence: 99%
“…To measure healthrelated quality of life (HR-QoL), the Haemo-QoL Index was used [15]. The Haemo-QoL Index is the short-form of the Haemo-QoL questionnaire, which was specifically developed for use in children with haemophilia (aged [4][5][6][7][8][9][10][11][12][13][14][15][16] and demonstrated good psychometric properties [16,17]. Due to the extensive nature of the original Haemo-QoL questionnaires (64-77 items), a short-form was chosen.…”
Section: Measurement Proceduresmentioning
confidence: 99%